Analysing English metaphors of the economic crisis - Filippo-Enrico Cardini (Lingue e Linguaggi, 2014)
Abstract - The present article reports the findings of an investigation into the metaphorical expressions adopted by English-language magazines to describe the latest economic/financial crisis. The corpus used for the investigation was about 100,000 words large, with texts taken from The Economist and from The International Economy. All the articles selected from these two magazines were published between Fall 2008 and Winter 2012. The main aim of the inquiry was to offer a more detailed and comprehensive classification of economic-crisis-metaphors than those proposed in previous research. In this respect, a total number of forty different types of such metaphors was identified. Alongside the theoretical classification, a quantitative analysis of the data was also carried out in order to find out which kinds of metaphorical expression are used most frequently. Results suggest that the economic/financial crisis is predominantly conceptualized in terms of something negative about a human being, about an object, and about a motion. In particular, viewing a state of economic/financial crisis as a damaged or destroyed object appears to be the most widely adopted metaphor. Results also suggest that different economics magazines can vary significantly in the amount of metaphorical language used. Keywords: metaphor, economic crisis, semantics, pragmatics, journalistic styles.   Sommario – Questo articolo riporta i risultati di una ricerca sulle metafore adottate da riviste in lingua inglese per descrivere la recente crisi economica e finanziaria. Il corpus utilizzato per l’indagine è stato di circa 100.000 parole, con testi reperiti dal The Economist e dal The International Economy. Tutti gli articoli selezionati da queste due riviste sono stati pubblicati tra l’autunno 2008 e l’inverno 2012. Lo scopo principale dell’indagine è stato quello di fornire una classificazione delle metafore della crisi economica più dettagliata ed esauriente di quelle proposte in ricerche precedenti. In questo senso sono stati individuati complessivamente quaranta differenti generi di metafora. Parallelamente a questa classificazione teorica è stata anche condotta un’analisi quantitativa dei dati nell’intento di individuare i tipi di espressione metaforica usati più frequentemente. I risultati suggeriscono che la crisi economica finanziaria è prevalentemente pensata come qualcosa di negativo riguardante un essere umano, un oggetto e un movimento. In particolare, la metafora più ricorrente sembra essere quella in cui lo stato di crisi economica viene riportato come un oggetto danneggiato o distrutto. I risultati indicano anche che riviste economiche differenti possono variare sensibilmente nella quantità di linguaggio metaforico utilizzato. Parole chiave: metafora; crisi economica; semantica; pragmatica; stili giornalistici.